46.5k views
3 votes
What is the correct answer for this equation? 6 ÷ 2(1+2) =

2 Answers

4 votes

The correct answer is 9

First you have to divide 6/2 is 3

Then you distribute 3 into the parentheses

3(1+2) = (3*1)+(3*2)

Then you solve

(3*1)=3

(3*2)=6

So,

6+3=9

User Kashif Ahmed
by
6.5k points
3 votes

Answer:

9

Explanation:

6 ÷ 2(1+2)

= 6 ÷ 2 x 3

= 3 x 3

= 9

User Ariefbayu
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.